Students’ Perspectives on Learning English through Social Communication in Social Media - Rosi Anjarwati; Lailatus Sa’adah (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2023)
Significant growth of social media use has created powerful impact on English language learning. This study examines the EFL learners’ perspectives on using social media through social communication for English language learning purposes to understand better how English learners perceive social media. For this purpose, 338 (158 males and 180 female) learners from 19 towns in East Java participated in a survey and responded to the questions of (1) what preference of social media used by different genders and (2) how is their perception toward the influence of social communication in social media on their language learning. Based on the findings, the students positively perceive the use of social media in learning English. Among many social media platforms, both male and female students share a similar preference; WhatsApp and Instagram are social media that EFL learners commonly use. The activities they prefer is dealing with receptive skills as they listen to songs or watch videos. Furthermore, both male and female students shared similar perceptions of the influence of social media on their English language skills, although there is a slight difference.